ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KSP. KOPDIT GURU KELUBAGOLIT CABANG WAIWERANG - Betria Mayanes, Angelita; Herdi, Henrikus; De Romario , Fransiscus (Jurnal Projemen UNIPA, 2025)
This research aimed to analyze financial statements to asses the financial performance of the credit union. The resurch used a quantitative approach using interviews and documentation techniques for data collection. The analysis method applied involves financial ratios, including liquidity ratio, proofitability ratio, and activity ratio. The result showed that the likuidity ratio calculations from 2022 to 2024 generally indicate good performance, with values ranging between 175%-200%. The solvency ratio calculations for the same period also demonstrated fairly good performance, with percentage above 80%. The profitability ratio calculation from 2022 to 2024 showed fairly good results, ranging between 50%-60%. Meanwhile, the activity ratio calculations from 2022 to 2024 revealed excellent performance, with values below 40%.